Over 3 million farmers could benefit from the first projects of a new initiative - Leta, S. (International Livestock Research Institute, 2011)
Seyoum Leta (Bio-Innovate, Program Manager) summarized that small-scale farmers in 6 East African countries will be the first in the region to benefit from the new Bio-Innovate program. The first projects in the scheme will tackle challenges like the development of more productive varieties of staple crops, and waste re-cycling. Over the next 5 years, the numbers of projects will expand, using Bio-Innovate's promotion of improvements in policy frameworks, its networks of scientists and research organizations, and the novel links it is building with private sector companies.